Numerical solution of viscoelastic fluid‐structure‐diffusion systems with applications in ophthalmology - Drobny, Alexander; Friedmann, Elfriede (Proceedings in applied mathematics and mechanics, 2019)
The research of fluid‐structure interaction problems is a continuously growing field, especially regarding applications in medicine and biology. We present the coupling of a potentially viscoelastic fluid with multiple hyperelastic structures incorporating chemical processes in the arbitrary Lagrangian Eulerian framework.